Autophagy Deficiency in Macrophages Enhances NLRP3 Inflammasome Activity and Chronic Lung Disease Following Silica Exposure - Jessop, Forrest (Toxicol Appl Pharmacol, 2016)
Autophagy is an important metabolic mechanism that can promote cellular survival following injury. The specific contribution of autophagy to silica-induced inflammation and disease is not known. The objective of these studies was to determine the effects of silica exposure on the autophagic pathway in macrophages, as well as the general contribution of autophagy in macrophages to inflammation and disease. Silica exposure enhanced autophagic activity in vitro in Bone Marrow derived Macrophages and in vivo in Alveolar Macrophages isolated from silica-exposed mice. Impairment of autophagy in myeloid cells in vivo using Atg5(fl/fl)LysM-Cre(+) mice resulted in enhanced cytotoxicity and inflammation after silica exposure compared to littermate controls, including elevated IL-18 and the alarmin HMGB1 in the whole lavage fluid. Autophagy deficiency caused some spontaneous inflammation and disease. Greater silica-induced acute inflammation in Atg5(fl/fl)LysM-Cre(+) mice correlated with increased fibrosis and chronic lung disease. These studies demonstrate a critical role for autophagy in suppressing silica-induced cytotoxicity and inflammation in disease development. Furthermore, this data highlights the importance of basal autophagy in macrophages and other myeloid cells in maintaining lung homeostasis.